Zika Virus: An Emerging Global Health Threat - Mittal, Rahul; Nguyen, Desiree; Debs, Luca H.; Patel, Amit P.; Liu, George; Jhaveri, Vasanti M.; S. Kay, Sae-In; Mittal, Jeenu; Bandstra, Emmalee S.; Younis, Ramzi T.; Chapagain, Prem; Jayaweera, Dushyantha T.; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Zika virus (ZIKV) is an emerging healthcare threat. The presence of the mosquito Aedes species across South and Central America in combination with complementary climates have incited an epidemic of locally transmitted cases of ZIKV infection in Brazil. Viremic international visitors have now dispersed ZIKV to at least 13 additional countries. As one of the most significant current public health concerns in the Americas, ZIKV epidemic has been a cause of alarm due to its known and unknown complications. At this point, there has been a clear association between ZIKV infection and severe clinical manifestations, including but not limited to neurological defects such as microcephaly in neonates and Guillain-Barré syndrome (GBS) in adults. The gravity of the fetal anomalies linked to ZIKV vertical transmission from the mother has prompted a discussion on whether to include ZIKV as a formal member of the TORCH (Toxoplasma gondii, other, rubella virus, cytomegalovirus (CMV) and herpes) pathogens known to breach placental barriers and cause congenital disease in the fetus. The mechanisms of these complex phenotypes have yet to be fully described. As such, diagnostic tools are limited and no effective modalities are available to treat ZIKV. This article will review the recent advancements in understanding the pathogenesis of ZIKV infection as well as diagnostic tests available to detect the infection. Due to the increase in incidence of ZIKV infections, there is an immediate need to develop new diagnostic tools and novel preventive as well as therapeutic modalities based on understanding the molecular mechanisms underlying the disease. Key words: Zika Virus; Pathogenesis; Animal models of Zika virus; Zika virus proteins